ANALISIS NILAI-NILAI PANCASILA DALAM TRADISI PENGANTIN SAHUR DI DESA PULAU PALAS KECAMATAN TEMBILAHAN HULU KABUPATEN INDRAGIRI HILIR - Lukman Fatwa; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted with the aim to find out how the values of Pancasila contained in the Pengantin Sahur tradition in Pulau Palas village, Tembilahan Hulu Subdistrict, Indragiri Hilir District. Data collection techniques are using two data, first is primary data through observation and interviews and the second is secondary data through library research and documentation.The results of the study showed that the values of the Pancasila that were appropriate at the time were not appropriate in the tradition of Pengantin Sahur in the village of Pulau Palas, Tembilahan Hulu, Indragiri Hilir district.The results showed that the values of the Pancasila in the bride sahur tradition were contained in the village of Pulau Palas, Tembilahan Hulu, Indragiri Hilir district. As for the values of the Pancasila found in the Pengantin Sahur tradition, namely on the value of divinity, in the tradition of the Pengantin Sahur before the event begins, always a prayer is made to be given fluency. This is the value of divinity and the value of trust in the creator. Human values, by respecting the rights of others in expressing their opinions and listening together. The value of unity, in the tradition of bride and groom, participates and participates in mutual cooperation to succeed the Pengantin Sahur tradition. The value of deliberation, the value of deliberation is always applied in order to reach consensus. Social value, seen from the cooperation of the government and the community in making bride the sahur happy.Key Words: Pancasila Values, Pengantin Sahur